Edukasi Tentang Manfaat Menikah Ta’aruf Melalui Komunikasi Antarpribadi Pada Mahasiswa Kampus Widyaloka Palu - Zainuddin, Sumarni; Adrian, Donal; Wahid, Muhammad; Utama, Roman Rezki; Jafar, Mohamad; Ramadhan, Moch. Rezky; Fadli, Magfirah Atsari Ayu; Tampubolon, Romaulina (Universitas Pahlawan Tuanku Tambusai, 2024)
Ta'aruf is a form of interpersonal communication between men and women who want to get to know each other before getting married. Ta'aruf, in the context of marriage, is a process of introduction facilitated by a companion in meeting between prospective husband and wife. Getting married according to Islamic law is a good thing because it avoids adultery, because many Muslims are found to prefer the dating process first and even get pregnant and then get married. This is certainly not a good thing, so it is necessary to provide education to teenagers in this case students of the Widyaloka Palu Campus to be wiser in behaving and to be able to follow Islamic law if they want to get married, of course by utilizing good communication between men and women. Based on the results of education, in Indonesia the concept of ta'aruf has begun to be applied by Muslim circles with the aim that Muslims know how to properly ta'aruf in order to get married based on Islamic law. The initial process of ta'aruf is to exchange information not directly but through the intermediary of biodata between candidates given to the mediator. Ta'aruf marriages in Palu City are widely carried out by Muslims who do indeed aim to get married for worship. It was further explained that Widyaloka Palu students then understood very well about the benefits of ta'aruf, namely to be able to avoid sins such as adultery. Marriage that goes through the ta'aruf process can certainly bring both people closer to the Creator because the relationship they do as a husband and wife aims to worship Allah SWT.